Analysis of a circular patch antenna radiating in a parallel-plate radial guide. - Bialkowski, M.E.
This paper investigates the use of a coaxially fed patch as a feeding element in a single-layer radial line slot antenna (RLSA) array. A field matching method is described to analyze a recessed circular cavity radiating into a radial waveguide. Using the wall impedance approach, the analysis is divided into two separate problems of the cavity and its external environment. Based on this analysis, a computer algorithm is developed for determining wall admittances as seen at the edge of the patch in the cavity, the radial admittance matrix for the two-probe feed arrangement, and the input impedance as observed from the coaxial line feeding the cavity. This algorithm is tested against the general-purpose Hewlett-Packard finite-element high frequency structure simulator as well as against measured results. Good agreement in all considered cases is noted
Keywords: RLSA; Circular patch antenna; Coaxial feed; Field matching method; Input impedance; Parallel-plate radial guide; Radial admittance matrix; Recessed circular cavity; Single-layer radial line slot antenna array; Wall admittances; Wall impedance approach